2017
DOI: 10.21577/0103-5053.20170150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenite and Selenate Application on Mineral Composition of Lettuce Plants Cultivated Under Hydroponic Conditions: Nutritional Balance Overview Using a Multifaceted Study

Abstract: The effect of selenate and selenite enrichment on mineral composition of a red type of lettuce cv. "Veneza roxa" was evaluated using inductively coupled plasma-optical emission spectroscopy (ICP OES), molecular modeling and principal component analysis (PCA). Both Se species did not show toxicity, while selenate promoted the greatest Se accumulation by the plant. There was an increase of 886 µg of Se per 100 g of fresh sample at different concentrations of selenate, but for selenite the maximum variation was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…Similarly, Smoleń et al (2016b) found a decrease in potassium content by about 9% in green butterhead lettuce leaves treated with selenium combined with iodine. On the other hand, the increase of K and Mg recorded in red Salanova treated with Se was in disagreement with other scientific literature where the authors found no variation in these two macroelements content after selenate applications (Wu and Huang, 1992; Silva et al, 2018a).…”
Section: Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…Similarly, Smoleń et al (2016b) found a decrease in potassium content by about 9% in green butterhead lettuce leaves treated with selenium combined with iodine. On the other hand, the increase of K and Mg recorded in red Salanova treated with Se was in disagreement with other scientific literature where the authors found no variation in these two macroelements content after selenate applications (Wu and Huang, 1992; Silva et al, 2018a).…”
Section: Resultscontrasting
confidence: 95%
“…Anyhow, Se leaf content was significantly higher than the control treatment in treatments ≥ 16 µM dose for both cultivars. Our results are in agreement with previous studies on red and green-pigmented lettuce (Ramos et al, 2010; Hawrylak-Nowak, 2013; Silva et al, 2018a) demonstrating the actual feasibility of using lettuce crop in Se biofortification programs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations